A Convoluted Frequency Selective Surface for Wideband Communication Applications - Shahid Habib; Ghaffer Iqbal Kiani; Muhammad Fasih Uddin Butt (IEEE Access, 2019)
A wideband bandstop frequency selective surface (FSS) for electromagnetic interference (EMI) reduction applications is presented for the S-, C-, and X-bands. The proposed FSS is made of convoluted square and circular loop elements, which are employed on the opposite surfaces of the RO3010 substrate. The overall dimensions of the FSS are reduced to 0.15λ at the center frequency compared with the conventional loop elements with an overall decrease in the size of more than 90% at the center frequency. It has a bandwidth of 9 GHz to reduce the harmful effects on the human body due to EMI caused by radio transceivers. It can also be employed as a sub-reflector to enhance the gain and the bandwidth of the antennas. Furthermore, it has many advantages in comparison to the designs presented in the latest research. For example, it has a low profile, the fractional bandwidth is enhanced up to 120%, and it ensures better angular stability for transverse electric (TE) as well as transverse magnetic (TM) polarized waves. Moreover, an average signal attenuation of more than 30.60 and 19.5 dB is ensured in the entire band for TE and TM modes, respectively. The simulation results are obtained using a high-frequency structure simulator (HFSS) and validated through the experimental results.